Dissociative episode secondary to hypoglycemic state in anorexia nervosa: a case report - Musa, Ramli; Almashoor Syed, Hassan; Sarkarsi, Rosnani (Wiley Online, 2009)
Objective: Hypoglycemic attack had been reported as one of the medical complications in anorexia nervosa. Method: We present a 25-year-old man who was diagnosed earlier with anorexia nervosa, presented with an episode of dissociative state during which he was caught for shoplifting. Results: In the history, he had a few episodes of fainting spells, which are most possibly due to hypoglycemia. There was no evidence to suggest any misdeeds to support that the stealing was intentional. Conclusion: Hypoglycemic attack may be common in anorexia nervosa, but this is a rare case with medico-legal implication.